Reflections on the “Policy-Relevant Turn” in Research - Garvin, Theresa (Social justice, 2003)
Part of a special issue on applied research and social justice. The consequences for sociology of the growing pressure on the discipline to be policy-relevant are discussed. The goals and advantages of the policy-relevant turn and the additional tensions and challenges that this obligation places on sociologists are considered.